أهمية الذكاء الاصطناعي في تحقيق التنمية الزراعية دراسة حالة الصين (2005/2023) - ثابت رقية; فريد كروش; سعيد عمار (جامعة الوادي University Of Eloued, 2025)
"هدفت الدراسة إلى قياس أثر الإستثمار في الذكاء الاصطناعي على التنمية الزراعية، من خلال دراسة حالة الصين في الفترة بين 2005 إلى غاية 2023، حيث عرفت الصين عدة تحولات كبيرة في القطاع الزراعي، فلجأت إلى تقنيات الذكاء الاصطناعي لمواجهة التحديات المتعلقة بالإجهاد الزراعي، مثل ندرة المياه وتغير المناخ وتناقص الأراضي الصالحة للزراعة. ركزت الدراسة على أساليب المستعملة من أجل الاستثمار في الذكاء الاصطناعي لتحسين الإنتاجية، وإدارة الموارد والتنبؤ بالمخاطر الزراعية مما ساهم في دعم النمية المستدامة للقطاع الزراعي، وتبرز التجربة الصينية كنموذج رائد في دمج التكنولوجيا الذكية لتحقيق أمن غذائي طويل الأمد وتقليل آثار الإجهاد الزراعي. The study aimed to measure the impact of investment in artificial intelligence on agricultural development, through a case study of China during the period from 2005 to 2023. China has undergone significant transformations in the agricultural sector and turned to artificial intelligence technologies to address challenges related to agricultural stress, such as water scarcity, climate change, and the decline of arable land. The study focused on the methods used to invest in artificial intelligence to improve productivity, manage resources, and predict agricultural risks, which contributed to supporting the sustainable development of the agricultural sector. The Chinese experience stands out as a leading model in integrating smart technologies to achieve long-term food security and reduce the effects of agricultural stress.
ماستر
Keywords: ذكاء اصطناعي; تنمية زراعية; صين; Artificial Intelligence – Agricultural Development – Agricultural Stress – China